STUDENTS’ PERCEPTION OF DIGITALLY-MEDIATED PEER TUTORING IN WRITING CLASS - Monika Prisila; Didi Suherdi (Edusentris, 2022)
Due to the impact of the corona pandemic, schools now provide instruction and training online. Given that the pandemic has already spread to every region of the globe, educators are urging students to become more proficient in the use of various digital technologies. In one of the West Kalimantan universities, the educational process is supported by digital technology. However, classes are frequently conducted on a large scale, making it challenging for instructors to keep track of their students. Consequently, a small teacher or peer tutor is required as an alternative to the provision of traditional extension classes or the invitation of additional writing instructors in order to assist every student with their individual writing difficulties. Twenty-three third-semester students enrolled in the English study program will be surveyed and interviewed for the purpose of this qualitative study. According to the findings of the study, the students' writing skills improved. Additionally, students responded positively to the use of digitally-mediated peer tutoring in writing classes. Therefore, digitally-mediated peer tutoring can be an option for meeting the needs of online learners.